STRATEGI PEMASARAN JAMUR TIRAM DALAM MENINGKATKAN VOLUME PENJUALAN DITINJAU DARI PERSPEKTIF EKONOMI SYARIAH (Studi Kasus Di Roemah Jamoer Ikram Desa Puringan Kecamatan Teluk Keramat) - Asmija Ika Bella; Oskar Hutagaluh, Jum’an (ADISAM PUBLISHER, 2024)
Marketing strategy is making decisions about costs, marketing, marketing mix, marketing allocation in relation to expected environmental conditions and competitive conditions. Marketing strategy is very important to measure the success of a business. The marketing strategy applied at Roemah Jamoer Ikram is well, it could be sent from the 3 (Three) years ago that production could be continued to grow so that it creates new products such as Jamur Crispy. This study aims to determine the marketing strategy in increasing sales volume and sharia economic review in the marketing strategy of Jamur Tiram in Roemah Jamoer Ikram.This research uses a descriptive qualitative approach and includes the type of case study research. Data collection techniques used are observation, interview, and documentation. The primary data source is the owner of Jamur Tiram production in Roemah Jamoer Ikram and the secondary data source is from written sources relating to the marketing strategy of Jamur Tiram. Research data analysis techniques are data reduction, data presentation, and conclusions or verification of research data. The data techniques used are the degree of confidence and continuous observation.Based on the results of the study concluded that Roemah Jamoer Ikram has implemented a marketing mix strategy that uses 5P variable are Product, Price, Place, Promotion, and People. Based on viewed by the perspective of sharia economics related to marketing strategies at Roemah Jamoer Ikram, it has implemented what the prophet Muhammad Saw, namely by prioritizing the nature of: Shiddiq, Amanah, Fathanah, Tabligh, and Istiqamah